Vitamin D Supplementation in Mechanically Ventilated Patients in the Medical Intensive Care Unit. Issue 8 (12th February 2019) - Leclair, Timothy R.; Zakai, Neil; Bunn, Janice Y.; Gianni, Michael; Heyland, Daren K.; Ardren, Sara S.; Stapleton, Renee D.
Abstract: Background: The utility of vitamin D (VITD) supplementation during critical illness and whether it may alter outcomes, including mortality and ventilator‐free days, is unclear. We performed a retrospective cohort study in a generalizable population to investigate this question. Methods: We included all mechanically ventilated adults admitted to the medical intensive care unit (ICU) service at a tertiary center from 2009 to 2012 who were in the ICU for at least 72 hours. Patients were grouped as having received or not received VITD at any time during the first 7 days of their ICU stay, and we adjusted for the following covariates with multivariable analyses: simplified acute physiology score, age, gender, admission diagnosis, race/ethnicity, admission season, admission day of the week, and VITD supplementation prior to admission. Results: Among the 610 included patients, 281 received VITD, and 329 did not. There were no differences in outcomes between these groups. However, we did find significantly more ventilator‐free days (21.0±2.6 [adjusted mean days±standard error] vs 17.6±2.4, P =0.04) and ICU‐free days (18.5±2.5 vs 16.3±2.3, P =0.03) in patients who were taking VITD prior to admission (n=91) vs those who were not (n=519). No patients who were taking VITD before admission died vs 34.5% of those who were not (estimated odds ratio=4.9×10 −7, 95% CI=3.1×10 −7 to 7.5×10 −7, P <0.0001). Conclusion: These results suggest that VITD supplementation during critical illness may not provide benefit and that further research investigating potential supplementation in ambulatory patients at high risk of ICU admission (eg, severe underlying chronic disease) is warranted.